Dendritic cell mediated mucosal cross talk - Ruane, Darren (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2013)
Developing efficacious vaccines against enteric diseases is a global challenge and priority. The rational design of such vaccines requires that novel pathways of cellular recruitment to the gastrointestinal (GI) tract be explored. The current paradigm of T cell homing to the GI tract involves the induction of a4β7 and CCR9 by Peyer's patch (PP) and mesenteric lymph node (MLN) dendritic cells (DC) in a retinoic acid (RA) dependent manner. To examine alternative pathways of cellular migration to the GI tract, we have examined the ability of lung DC (LDC) to recruit lymphocytes to the GI tract. Using a DC:OT-II co-culture system, we have identified that LDC (both CD 103- and CD 103+) up regulate gut homing integrin a4β7 in vitro and induce T cell migration to the GI tract in vivo. LDC mediated a4β7 induction required retinoic acid and TGF-β signaling. Significantly, targeting of LDC by intranasal immunization induced protective immunity against enteric challenge with a highly pathogenic strain of Salmonella typhimurium. The present report demonstrates the presence of significant mucosal cross talk mediated by DCs. Additionally; we define a novel pathway of lymphocyte migration to the GI tract, which potentially paves the way for rational design of vaccines against mucosal pathogens
Keywords: Biochemistry & Immunology, Ph.D.; Ph.D. Trinity College Dublin.